The Eighth Grade Student’s Errors in English Sentence Patterns at MTs Al-Islami Tugasari Kurungan Nyawa I OKU Timur - Iswahyudii, Iswahyudi; Franzhardi, Didi; Natalia, Sugiani (ENJEL: English Journal of Education and Literature, 2022)
The title of this thesis is “The eighth grade Students errors in English sentence patterns at MTs Al-Islami Tugasari Kurungan Nyawa 1 OKU Timur”. The main problems of this thesis were What are the students’ errors in using sentence pattern and What is factor made the errors by the students ? Therefore the objectives of this research were To know what kinds of error that made by the students in using sentence pattern and find out the Eighth grade students' error in English sentence patterns, and to know the possible cause made by the Eighth grade students’ The population of this research was the eighth year students at MTs Al-Islami Tugasari Kurungan Nyawa 1 OKU Timur in the academic year of 2011/2012 and the sample of this study was 35 students taken randomly by using cluster sampling. The method of this study was the descriptive method. To collect the data, the writer used written test. The results of the test were analyzed descriptively.The findings show the students made errors in using conjunctions with the Subordinating sentence patterns; “object” (40.57%), “adverb” (42%), and “complement” (39.43%). The average on the percentage of students errors was 40.66% on the written test.